1998
DOI: 10.1021/cm9707519
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acidic Borane Adducts of Pyridines and Stilbazoles for Nonlinear Optics

Abstract: A series of neutral pyridyl adducts involving the strong Lewis acids BF 3 and B(C 6 F 5 ) 3 has been prepared, and their second-order nonlinear optical coefficients (EFISH method) have been examined. The formation of the pyridyl-boron bond leads to enhancement of the dipole moments and second-order NLO coefficients (β and β(0)). Reactions of DMAP (4-Me 2 N-C 5 H 4 N) with BH 3 , BF 3 , and B(C 6 F 5 ) 3 give the corresponding neutral pyridine adducts DMAP‚-BH 3 (orthorhombic, Pbca, a ) 9.6914(7) Å; b ) 11.7173… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
101
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 39 publications
13
101
0
3
Order By: Relevance
“…The proton resonances of the organic ligands bound to the metal centers appear further downfield (MeAl, EtAl, and Me 3 Si resonances) than those of the starting heterocycles, while those of the dmap molecule are shifted upfield. These findings are in agreement with results observed for similar borane adducts, [12] and correspond to a partial rearrangement of the charge distribution within the aromatic ring as shown in Scheme 2. (1) As found in the corresponding monomers of the higher homologues dmapϪAl(R 2 )E(SiMe 3 ) 2 (R ϭ Me, Et, E ϭ Sb, Bi), [3,4] the substituents bonded to Al and the particular pentele atom adopt a staggered conformation relative to are at the lower end of typical EϪSi bond lengths.…”
Section: Resultssupporting
confidence: 92%
“…The proton resonances of the organic ligands bound to the metal centers appear further downfield (MeAl, EtAl, and Me 3 Si resonances) than those of the starting heterocycles, while those of the dmap molecule are shifted upfield. These findings are in agreement with results observed for similar borane adducts, [12] and correspond to a partial rearrangement of the charge distribution within the aromatic ring as shown in Scheme 2. (1) As found in the corresponding monomers of the higher homologues dmapϪAl(R 2 )E(SiMe 3 ) 2 (R ϭ Me, Et, E ϭ Sb, Bi), [3,4] the substituents bonded to Al and the particular pentele atom adopt a staggered conformation relative to are at the lower end of typical EϪSi bond lengths.…”
Section: Resultssupporting
confidence: 92%
“…Remarkably, some of the boranepyridine adducts have interesting nonlinear optical properties. [4] Recently, Wang and co-workers have demonstrated that irradiation of adducts such as A leads to the formation of B, which contains a boracyclopropane ring with the B À N linkage remaining intact (Scheme 1). [5] Analogous rearrangement reactions have been found during photolysis of tetraphenylborates, where the generation of free radical species has also been observed (Scheme 1).…”
mentioning
confidence: 99%
“…After purification on silica with diethyl ether as an eluent, a yellow powder was obtained which was recrystallised from diethyl ether/hexane mixture to give the product (0.141 g, 31 %). [44] Synthesis of the fac-[Re(CO) 3 (HT)A C H T U N G T R E N N U N G (phen)] complexes: These complexes were prepared based on established literature procedures. [6,16,18,33,45] Commercially obtained [Re(CO) 5 Cl] (Aldrich) and 1,10-phenanthroline·H 2 O (Aldrich) were heated under refluxed in absolute ethanol to give fac-[Re(CO) 3 ClA C H T U N G T R E N N U N G (phen)].…”
Section: Methodsmentioning
confidence: 99%